Synthesis and structure of novel tripodal ligands based on tetrazol-5-thioles - Voitekhovich, Sergei V.; Degtyarik, Mikhail M.; Lyakhov, Alexander S.; Ivashkevich, Ludmila S.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2022)
Novel tripodal ligands (R1N4CS)3CH, where R1 = Me, Ph, were synthesised by alkylation of 1-R-tetrazol-5-thioles with iodoform in alkaline media. These ligands were identified based on data of elemental analysis, nuclear magnetic resonance spectroscopy, thermal analysis, and X-ray diffraction analysis of single crystals.
Keywords: multipodal ligands; tetrazol-5-thioles; alkylation; X-ray diffraction analysis